PENGARUH BRAND IMAGE DAN CUSTOMER VALUE TERHADAP REPURCHASE INTENTION MELALUI CUSTOMER SATISFACTION - Pramesti, Adia Beta; Waloejo, Handoyo Djoko (Jurnal Ilmu Administrasi Bisnis, 2019)
Phenomena of consuming restaurants product alongside the nowadays trend to just having time with family or friends in restaurants as well as the resident’s habit in prefer having things quickly, easily and practically. As one of restaurant in Semarang, Waroeng SS serves Indonesian food as its main dish demands the customer to have the urge to repurchase as it outcome. The aims of this study is to measure the effects of brand image and customer value to repurchase intention through customer satisfaction. The type of this research is explanatory research. Sampling techniques using purposive and accidental sampling. Population of this research is consumers of Waroeng SS Tembalang I. The data was analyzed using SPSS 21.0 for Windows.